Production of Biogas From a Mixture of Chicken Litter and Cow Manure and Its Effect on the Resulting Volume and C/N Ratio - Tira, Hendry; Sutanto, Rudy (Jurnal Pijar Mipa, 2024)
The livestock sector's waste is a potential raw material for producing biogas because it is abundantly available. This experiment aimed to understand the potential of two types of livestock waste to produce biogas. The two sources of raw material were mixed with different variations. The results showed that the volume of fermentation gas produced from livestock waste varied depending on the type and composition of the raw material used. Mixing was done to determine the best variation in producing biogas from chicken litter and cow manure. The volume ratio of litter to cow manure used was (0%:100%), (25%:75%), (50%:50%), (75%:25%), (and 100%:0%), with a total volume of 2 liters. In addition, 10% of EM-4 (effective microorganism) was added to the mixture of livestock waste that had previously been given 2 liters of water. The waste mixture was then fermented for 30 days. The fermentation process was carried out under mesophilic conditions at room temperature and pressure. This study showed that the higher the concentration of chicken litter in the mixture, the higher the carbon-to-nitrogen (C/N) ratio value. On the other hand, if there is a higher composition of cow manure in the mixture, the substrate pH value will be higher. Furthermore, a 50%:50% composition of chicken litter and cow manure produced a high volume of biogas. Similarly, the biogas formation rate in this composition showed the best performance. These results prove that the balance of carbon and nitrogen composition, temperature, and substrate acidity significantly affect biogas production.